1998
DOI: 10.1093/emboj/17.22.6622
|View full text |Cite
|
Sign up to set email alerts
|

Integrins induce activation of EGF receptor: role in MAP kinase induction and adhesion-dependent cell survival

Abstract: Adhesion of human primary skin fibroblasts and ECV304 endothelial cells to immobilized matrix proteins, β1 or αv integrin antibodies stimulates tyrosine phosphorylation of the epidermal growth factor (EGF) receptor. This tyrosine phosphorylation is transiently induced, reaching maximal levels 30 min after adhesion, and it occurs in the absence of receptor ligands. Similar results were observed with EGF receptor-transfected NIH-3T3 cells. Use of a kinasenegative EGF receptor mutant demonstrates that the integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
405
8
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(441 citation statements)
references
References 66 publications
23
405
8
5
Order By: Relevance
“…In PC3 cells, integrin-mediated activation of c-Met was not dependent on Src activity. Prior studies indicate that ligand-independent activation of receptor kinases is required for signaling downstream of integrins (Moro et al, 1998;Bill et al, 2004). However, we found that inhibition of c-Met had no effect on integrin-induced Src activation per se.…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Miranticontrasting
confidence: 59%
See 1 more Smart Citation
“…In PC3 cells, integrin-mediated activation of c-Met was not dependent on Src activity. Prior studies indicate that ligand-independent activation of receptor kinases is required for signaling downstream of integrins (Moro et al, 1998;Bill et al, 2004). However, we found that inhibition of c-Met had no effect on integrin-induced Src activation per se.…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Miranticontrasting
confidence: 59%
“…Both integrins and receptor tyrosine kinases are involved in cell migration and metastasis. Furthermore, integrins have been shown to activate several receptor tyrosine kinases in a ligandindependent manner, including EGFR, c-Met, PDGFR, and Ron (Sundberg and Rubin, 1996;Wang et al, 1996Wang et al, , 2001Moro et al, 1998Moro et al, , 2002Danilkovitch-Miagkova et al, 2000;Bill et al, 2004). Both integrins and receptor tyrosine kinases can interact with CD82 (Hemler, 1998;Odintsova et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) [63], hepatocyte growth factor receptor (HGFR) [64] vascular endothelial growth factor receptor (VEGFR) [65] and platelet-derived growth factor receptor (PDGFR) [66] are the main growth factor receptors recruited in integrin platforms. In epithelial cells, either ligand-dependent or integrin-mediated ligand-independent EGFR activation stimulates ERK and PI3K signalling, thereby suppressing the activity of apoptotic factors.…”
Section: Physiological Protection From Anoikismentioning
confidence: 99%
“…The ligand-independent phosphorylation of EGF receptor in response to integrin ligation is strictly dependent by its association with the adaptor protein p130Cas and the c-Src tyrosine kinase [63,68]. Src kinase is activated in response to integrin ligation due to its redox sensitivity.…”
Section: Physiological Protection From Anoikismentioning
confidence: 99%
“…Integrin activation of MAPK requires FAK autophosphorylation and c-Src activation [6], and has been proposed to involve SH2-mediated recruitment of the adapter protein Grb2 involved in growth factor activation of Ras to a site of c-Src phosphorylation (Y925) in FAK [7,8]. Alternatively, integrins may cooperate with growth factor receptors such as the PDGF, insulin and EGF receptors to activate their respective downstream signaling mechanisms [9][10][11]. However, while some laboratories find that Ras is required for ERK activation during adhesion [8,12,13], others find that inhibiting Ras is without effect on adhesion stimulated ERK activation [14,15].…”
Section: Erk Activation In Response To Growth Factors and Adhesion Simentioning
confidence: 99%